O sistema sócio-educativo de internação para jovens autores de ato infracional do estado de São Paulo - Teixeira, Joana D'arc (2009)
In late 90 s, in the State of São Paulo, proposals for reforms and decentralisation of FEBEM were presented and consolidated. In the course of restructuring public policies, the institution acquired the denomination: Fundação Centro de Atendimento Socioeducativo ao Adolescente FUNDAÇÃO CASA (Foundation Centre of Socio-educational Service for Adolescents). This research intends to describe, analyse and understand the restructuring process of the socio-educational system in order to contribute to the discussions and reflections about the modifications of the policies of the educational service to adolescents who commit criminal offences. Considering documentation analyses (period 1996-2009), the studies of researches about the topic and the theoretical approach adopted about the trends of control and punishment that emerges in contemporary society, total institutions and socioeducation, it is possible to indicate that the process of restructuring and amplification through which the institution undergoes must be understood out of a number of factors such as socio-political transformations, social-control, socio-educative proposal and the internal dynamics of the institution. Although the legislation determines the reduction of the confinement, the institutional reconfiguration and the increase of imprisonment of youth can be seen. Therefore, instead of a disruption in the institutionalization process and in the punitive aspects, what actually occurs is the displacement of the youth to a system that tends to legitimise their action, having as its base the main prerogatives of the child and adolescent s rights. The restructuring process, still in course, has not yet promoted practices of socioeducative service that comprehend different educative processes as well as social relationship, using as reference the values and principles of the constitution regarding the respect to human dignity.